2006
DOI: 10.1143/jpsj.75.051008
|View full text |Cite
|
Sign up to set email alerts
|

Charge Ordering in Organic Conductors

Abstract: Present status of experiments on charge ordering (CO) phenomena observed in organic molecular conductors is reviewed. Experimental techniques to detect and analyze the CO, i.e., NMR, X-ray and Infrared/Raman spectroscopy, are described and the experimental results in typical materials exhibiting CO are summarized. (DI-DCNQI) 2 Ag, (TMTTF) 2 X, -(BEDT-TTF) 2 I 3 , -(BEDT-TTF) 2 RbZn(SCN) 4 and related materials are discussed. Charge disproportionation without long-range order observed in numbers of materials ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
102
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 109 publications
7
102
1
Order By: Relevance
“…Namely, in the x-ray scattering experiment, diffuse sheets (or planes) along the 2a + c and the 2a − c directions are observed at room temperature below, which is considered to be due to the effect of anions (the diffuse sheets are shown in the lower panels of figures 5 and 7) [9]. Actually, the wave vectors ( 2 3 , k, 1 3 ) (a-axis three fold) and (0, k, 1 2 ) (horizontal stripe) are on these diffuse sheets, and they 'grow' from these sheets as the temperature is lowered, suggesting the relevance of the anions. Kuroki considered the effect of these diffuse sheets phenomenologically by adding a term that enhances the charge susceptibility along the line 2a + c to the denominator of equation (2), and he found that the maximum value of the charge susceptibility saturates at low temperatures [42].…”
Section: Future Problems Regarding the Competitionmentioning
confidence: 94%
See 4 more Smart Citations
“…Namely, in the x-ray scattering experiment, diffuse sheets (or planes) along the 2a + c and the 2a − c directions are observed at room temperature below, which is considered to be due to the effect of anions (the diffuse sheets are shown in the lower panels of figures 5 and 7) [9]. Actually, the wave vectors ( 2 3 , k, 1 3 ) (a-axis three fold) and (0, k, 1 2 ) (horizontal stripe) are on these diffuse sheets, and they 'grow' from these sheets as the temperature is lowered, suggesting the relevance of the anions. Kuroki considered the effect of these diffuse sheets phenomenologically by adding a term that enhances the charge susceptibility along the line 2a + c to the denominator of equation (2), and he found that the maximum value of the charge susceptibility saturates at low temperatures [42].…”
Section: Future Problems Regarding the Competitionmentioning
confidence: 94%
“…orderings and fluctuations have been one of the central issues in the physics of organic materials [1,2] 1 . θ-(BEDT-TTF) 2 X 1 The term 'charge ordering' is usually used in a sense that it is not related to the Fermi surface, while a 'charge density wave' occurs as a result of Fermi surface nesting.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations